Algorithm for Finding the Coefficients of Rook Polynomials: Vites Longani - Team, Support (Thai Journal of Mathematics, 2010)
In solving problems on finding the number of arrangements of n objects with restrictions, it is usually required to find the coefficients of certain polynomials called rook polynomials. See [1], [2], and [3] for topics on rook polynomials. It is not difficult to find these coefficients when n is not large. However, when n becomes larger the calculation becomes laboring and less practical. In this paper, we propose a simple algorithm for finding these coefficients. Also, this algorithm can be modified for more general problems on rook polynomials.